COMPUTER-EFFICIENT BINOMINAL MODEL OF DEFAULT DISTRIBUTION - Dmitry V. Bogdanov (Вестник Российского экономического университета имени Г. В. Плеханова)
The analysis of default correlation is especially acute in conditions of the current finance crisis. The article discusses examples of using the binominal model of default distribution in certain cases. The author formulated and proved the equation about types of correlations to solve the task of finding the function of distribution of default possibilities in the general case. This methodology can provide an opportunity to get the vector of elementary possibilities through the known set of max default possibilities of each company and max pair possibilities of default of interconnected companies as a solution for the system of linear and linear-logarithmic model of the system. The author offers ways to simplify the model of the system. The findings can be used both for risk management and credit derivatives in general.